Un-asking the question: Introducing a Critical Buddhist Analytic - Yoosun Park; Alicia Chatterjee (Social Work and Society)
In response to a call for a social work that reimagines the contours and content of the"social" (Wilson & Lynch, 2021, p. 1), we present two concepts central to Buddhism: Å›Å«nyatÄ (translated as"emptiness") and anÄtman (e"no-self"), the anti-essentialist concept of Å›Å«nyatÄ as applied to the subject. The negation of all dualisms"”the refutation of the anthropocentric, humanist world view, central concerns of the"new" posthumanisms"”are basic premises of Buddhism. Our intent is to point to: 1) the untapped conceptual/theoretical riches of Buddhism, and; 2) the example of the Mindfulness industry, which cautions us that while social work is willing to extract elements of historically marginalized onto-epistemologies to be incorporated into the existing knowledge base, that base is not intended to be decentered. We introduce Buddhism, not as a truer alternative, but as a radical heuristic for un-settling the onto-epistemologies of rationality, the human subject, and social work futurities.